Establishment and validation of a ubiquitination-related gene signature associated with prognosis in pancreatic duct adenocarcinoma - Guo, Yangyang; Wu, Zhixuan; Cen, Kenan; Bai, Yongheng; Dai, Ying; Mai, Yifeng; Hong, Kai; Qu, Liangchen (Frontiers in Immunology, 2023)
Abstract Background: Patients with pancreatic duct adenocarcinoma (PDAC) have varied prognoses that depend on numerous variables. However, additional research is required to uncover the latent impact of ubiquitination-related genes (URGs) on determining PDAC patients' prognoses. Methods: The URGs clusters were discovered via consensus clustering, and the prognostic differentially expressed genes (DEGs) across clusters were utilized to develop a signature using a least absolute shrinkage and selection operator (LASSO) regression analysis of data from TCGA-PAAD. Verification analyses were conducted across TCGA-PAAD and ICGC-PACA-AU to show the robustness of the signature. RT-qPCR was used to verify the expression of risk genes. Lastly, we formulated a nomogram to improve the clinical efficacy of our predictive tool. Results: The URGs signature, comprised of two genes, was developed and was shown to be highly correlated with the prognoses of PAAD patients. The nomogram was established by combining the URGs signature with clinicopathological characteristics. In contrast with the performance of the other individual predictors, we discovered that the URGs signature was remarkably superior. Also, the immune microenvironment analysis indicated that ESTIMATEscore, ImmuneScores, and StromalScores were elevated in the low-risk group. The immune cells that infiltrated the tissues were different between the two groups, as did the expression of immune-related genes. Conclusion: The URGs signature could act as the biomarker and provide a momentous reference for individual therapy of PDAC patients. Keywords: ubiquitination, PDAC, Immune microenvironment, Immunotherapy, Prognosis